Volume and colour development in cake baking process - Wan Ishak, Wan Illia; Taip, Farah Saleena; Bejo, Siti Khairunniza; Mustapa Kamal, Siti Mazlina (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Colour, crust browning and volume of a batter are among the important parameters in measuring the quality of cake. However, it is rarely measured directly during the baking process due to lack of suitable instrumentation. The objective of this study was to evaluate the development in browning and volume of cake during baking process. A computer vision based image analysis algorithm was developed to measure the colour of cake surface in CIE L*a*b* colourspace. Additionally, height profile method was used to measure the volume development of cake during this baking process. Baking experiments were performed at 170°C in three different stages: 20, 35, and 55 minutes under forced convection oven. Results showed that the variation in lightness of cake surface can be distinguished according to the baking time. As in volume development, there was rapid expansion during initial time of baking which followed by shrinkage towards end of baking.